Pengaruh Agama pada Masyarakat Indonesia: Kajian Sosiologis terhadap Dimensi Sosial, Pendidikan, Ekonomi, dan Politik - I Made Andika Widiatma; Daniyel Ninto Styawan (Jurnal Motivasi Pendidikan dan Bahasa, 2026)
This research aims to analyze in depth the influence of religion on the life of the Indonesian people in various dimensions, namely socio-cultural, educational, economic, and political. Indonesia as a multicultural country with a high level of religious diversity, including Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism, makes religion a fundamental element in the formation of social structure, national identity, and the direction of nation development. This diversity was formed through a long historical process, starting from the influence of Hindu-Buddhism during the royal period, the entry of Islam through trade routes, to the influence of Christianity and Catholicism during the colonial period. The research uses a descriptive-analytical approach with library research techniques sourced from scientific literature, academic books, journals, and official government reports. The main framework of analysis rests on the sociological theories of religion from classical figures such as Emile Durkheim, Max Weber, and Karl Marx, which are enriched with contemporary perspectives relevant to the Indonesian context. The results of the study show that religion not only functions as an individual belief system, but also as a social force that influences the patterns of community interaction, value systems, and public policies. In the socio-cultural dimension, religion is the foundation of norms and ethics that strengthen collective solidarity, reflected in various religious ceremonies such as Ngaben in Bali, Sekaten in Java, and Christmas celebrations in Christian communities.